CRISPR/Cas9-mediated gene targeting in Arabidopsis using sequential transformation - Miki, Daisuke; Zhang, Wenxin; Zeng, Wenjie; Feng, Zhengyan; Zhu, Jian-Kang (Nature communications, 2018)
Homologous recombination-based gene targeting is a powerful tool for precise genome modification and has been widely used in organisms ranging from yeast to higher organisms such as Drosophila and mouse. However, gene targeting in higher plants, including the most widely used model plant Arabidopsis thaliana , remains challenging. Here we report a sequential transformation method for gene targeting in Arabidopsis . We find that parental lines expressing the bacterial endonuclease Cas9 from the egg cell- and early embryo-specific DD45 gene promoter can improve the frequency of single-guide RNA-targeted gene knock-ins and sequence replacements via homologous recombination at several endogenous sites in the Arabidopsis genome. These heritable gene targeting can be identified by regular PCR. Our approach enables routine and fine manipulation of the Arabidopsis genome. Efficient gene targeting in higher plants remains challenging. Here, the authors develop a sequential transformation method for CRISPR/Cas9-mediated gene targeting in Arabidopsis and demonstrate its functionality at five genomic sites in two endogenous loci.